2020
DOI: 10.1363/psrh.12161
|View full text |Cite
|
Sign up to set email alerts
|

The Fine Line Between Informing and Coercing: Community Health Center Clinicians’ Approaches to Counseling Young People About IUDs

Abstract: CONTEXT While community health centers (CHCs) are meeting increased demand for contraceptives, little is known about contraceptive counseling in these settings. Understanding how clinicians counsel about IUDs in CHCs, including whether they address or disregard young people's preferences and concerns during counseling, could improve contraceptive care. METHODS As part of a training program, 20 clinicians from 11 San Francisco Bay Area CHC sites who counsel young people about contraception were interviewed by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 45 publications
1
23
0
Order By: Relevance
“…After LARC-focused education, many adolescent mothers will indicate a preference for LARC, 61 yet data from a recent study demonstrated that in a sample of mostly African-American adolescents, those with higher autonomy decision-making subscale scores were less likely to prefer LARC. 80 The promotion of LARC as a universally acceptable antidote to high adolescent pregnancy rates has received criticism due to inequitably high promotion of these devices to marginalized or priority communities, including teenagers 49 and women in developing countries, 81 and the user's reliance on providers for LARC insertion and removal. 82,83 While a lack of access to LARC amplifies unrealized sexual and reproductive health goals and limits individual autonomy and choice, so, too, can discriminatory promotion and inaccessible LARC removal, potentially leading to negative experiences of care and disengagement from the health system.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After LARC-focused education, many adolescent mothers will indicate a preference for LARC, 61 yet data from a recent study demonstrated that in a sample of mostly African-American adolescents, those with higher autonomy decision-making subscale scores were less likely to prefer LARC. 80 The promotion of LARC as a universally acceptable antidote to high adolescent pregnancy rates has received criticism due to inequitably high promotion of these devices to marginalized or priority communities, including teenagers 49 and women in developing countries, 81 and the user's reliance on providers for LARC insertion and removal. 82,83 While a lack of access to LARC amplifies unrealized sexual and reproductive health goals and limits individual autonomy and choice, so, too, can discriminatory promotion and inaccessible LARC removal, potentially leading to negative experiences of care and disengagement from the health system.…”
Section: Discussionmentioning
confidence: 99%
“…[46][47][48] However, researchers are concurrently attempting to understand adolescent decision-making and document the practices of healthcare professionals in the context of LARC provision, particularly to "high-risk" groups such as adolescents. 49 In a preliminary search of the literature we identified a relative lack of research on acceptability and personcentered outcomes despite increasing emphasis on IPP/IPA LARC. An autonomous contraception decisions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 28 , 29 , 30 Furthermore, adolescents who report receipt of contraceptive counseling are more likely to use a moderately or most effective method. 31 Counseling must always respect adolescent autonomy, 32 and counseling for adolescents must be tailored for developmental stage, information needs, and need for confidentiality. 8 , 11 …”
Section: Discussionmentioning
confidence: 99%
“…1 Several qualitative studies from the patient perspective have explored how provider bias can show up in contraceptive care, limiting the patient's ability to make fully voluntary choices. [2][3][4][5] In this study, we define contraceptive agency as the ability and capacity to decide about contraception, without undue influence, judgment, or coercion from healthcare providers. Contraceptive agency is especially important among patients in communities that have experienced reproductive harms, including from racism or contraceptive coercion in the healthcare system.…”
Section: Introductionmentioning
confidence: 99%